Legalitas Penjatuhan Sanksi Pidana dalam Putusan No. 378/PID.SUS/2022/PN.SMN ditinjau Berdasarkan Prinsip Ultra Petita - Sanny Nuyessy Putri; Ade Adhari (Dinasti Research, 2024)
Ultra Petita Decision refers to a court ruling made by a judge on a matter that was not requested or, in other words, a ruling in which the judge grants more than what was demanded. The judge's basis for issuing a criminal judgment is the indictment. The purpose of this research is to understand and analyze the legality of imposing criminal sanctions in Sleman District Court Decision No. 378/Pid.Sus/2022/PN.Smn and to examine the limitations of a judge's authority in issuing an ultra petita decision. The legal research method used is normative legal research. The approaches employed are the legislative approach and the case approach. The prohibition against issuing rulings beyond what is requested is the principle of ultra petitum partium. Decisions containing elements of ultra petita are considered flawed and lead to legal uncertainty. The public prosecutor can be deemed negligent in drafting the indictment, which may prompt a judge to issue a ruling beyond the indictment. The limitation of a judge's authority in issuing a decision lies in the indictment, which serves as the litis contestation. Thus, restrictions on a judge's authority to adjudicate cases must explicitly prohibit ultra petita. In this case, the indictment prepared by the public prosecutor regarding extortion committed by the defendant was inaccurate because the prosecutor focused solely on the dissemination of indecency. Legal principles must serve as the basis to consider when interpreting and discovering the law.